PENGARUH MEDIA PEMBELAJARAN BERBASIS TEKNOLOGI DAN MOTIVASI BELAJAR TERHADAP KREATIVITAS SISWA JURUSAN PERBANKAN SMKN 2 BOYOLANGU TULUNGAGUNG TAHUN AJARAN 2025/2026 - Thessa Faridah Az Zahra; Sulastri Rini Rindrayani (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT Student creativity is an essential competency that supports academic success and future career readiness. However, preliminary observations at SMKN 2 Boyolangu Tulungagung revealed that the creativity of students in the Banking program remains relatively low. This is indicated by the predominance of